Hubungan Aktivitas Fisik dan Daya Tahan Kardiovaskular Pada Mahasiswa Laki-Laki Tim Bantuan Medis Baswara Prada Angkatan 2018 dan 2019 - Made Billy Dwiki Saputra; IGB Gita Pranata Putra; Desak Putu Citra Udiyani (Aesculapius Medical Journal, 2022)
[Relationship Physical Activity and Cardiovascular Endurance In Male Students of 2018 and 2019 Baswara Prada Medical Assistance Team] Physical activity is a process of body movement created by muscles and utilizing energy. The prevalence of a minimal physical activity, the higher the number caused by the busyness of the students. This affects one of the building blocks of physical fitness, namely cardiovascular endurance. The aim of the study was to determine the correlation between physical activity and cardiovascular endurance in male students of the 2018 and 2019 Baswara Prada Medical Assistance Team. This study applied an observational study, and cross sectional design which included 51 male students of the 2018 and 2019 Baswara Prada medical assistance team. Data were collected by taking secondary Harvard step test data to measure cardiovascular endurance and primary data by fill the GPAQ survey to determine activity. physical. Data analysis used SPSS and level of significant is 0.05. As per results of Chi-square analysis, there was a significant correlation between the relationship between physical activity and cardiovascular endurance (p=0.000) in male students of the 2018 and 2019 Baswara Prada Medical Assistance Team.